Pengembangan Pendidikan Ekonomi Berkelanjutan untuk Sekolah Menengah Atas - - Wahjoedi; Gatot Sujono; Nunung Nurastuti; Endang Sri Handayani; Magistyo Purboyo Priambodo (Universitas Negeri Malang, 2013)
Abstract: The Development of Sustainable Economics Education for Senior High Schools. The focus of this first-year research of a multi-year study is portraying the implementation of economics education at senior high schools in East Java. Employing a survey design, this study involved 69 economics teachers. Interviews and questionnaires were utilized to obtain data concerning whether the practice of economics teaching reflects sustainable education. Existing relevant documents were also examined to provide supporting evidence. The findings show that sustainable economics education is not evident yet in the teachers' teaching practice as can also be seen from the curriculum, teachers' subject-matter understanding, teaching and learning processes, textbooks, and school atmosphere. These findings then become the basis for developing a model of sustainable economics education. Abstrak: Pengembangan Pendidikan Ekonomi Berkelanjutan untuk Sekolah Menengah Atas. Tujuan penelitian tahap pertama dari penelitian multi tahun ini adalah untuk mendeskripsikan tentang potret pelaksanaan pembelajaran ekonomi berkelanjutan di SMA  Jawa Timur. Melalui penelitian survai, data dikumpulkan dari 69 orang guru ekonomi SMA dengan cara wawancara dan penyebaran angket serta dukungan data dokumentasi, dapat disimpulkan bahwa pendidikan ekonomi berkelanjutan di SMA belum terlaksana. Belum terlaksananya hal tersebut tercermin pada muatan isi kurikulum, pemahaman dan kesiapan guru, inovasi proses pembelajaran, kondisi buku ajar, dan penataan suasana sekolah. Melihat kondisi tersebut diperlukan langkah perbaikan dengan segera melalui pengembangan pendidikan ekonomi berkelanjutan dengan pembelajaran yang lebih inovatif.